Developmental programming of tissue-resident macrophages - Viola, Maria Francesca; Franco Taveras, Eliana; Mass, Elvira (Frontiers in Immunology, 2024)
Macrophages are integral components of the innate immune system that colonize organs early in development and persist into adulthood through self-renewal. Their fate, whether they are replaced by monocytes or retain their embryonic origin, depends on tissue type and integrity. Macrophages are influenced by their environment, a phenomenon referred to as developmental programming. This influence extends beyond the local tissue microenvironment and includes soluble factors that can reach the macrophage niche. These factors include metabolites, antibodies, growth factors, and cytokines, which may originate from maternal diet, lifestyle, infections, or other developmental triggers and perturbations. These influences can alter macrophage transcriptional, epigenetic, and metabolic profiles, affecting cell-cell communication and tissue integrity. In addition to their crucial role in tissue immunity, macrophages play vital roles in tissue development and homeostasis. Consequently, developmental programming of these long-lived cells can modulate tissue physiology and pathology throughout life. In this review, we discuss the ontogeny of macrophages, the necessity of developmental programming by the niche for macrophage identity and function, and how developmental perturbations can affect the programming of macrophages and their subtissular niches, thereby influencing disease onset and progression in adulthood. Understanding these effects can inform targeted interventions or preventive strategies against diseases. Finally, understanding the consequences of developmental programming will shed light on how maternal health and disease may impact the well-being of future generations.